Serum C‐peptide and osteocalcin levels in children with recently diagnosed diabetes. Issue 1 (29th November 2019) - Sabek, Omaima M.; Redondo, Maria J.; Nguyen, Duc T.; Beamish, Christine A.; Fraga, Daniel W.; Hampe, Christiane S.; Mulukutla, Surya N.; Graviss, Edward A.; Gaber, A. Osama
Abstract: Background: We explored the association of C‐peptide (marker of secreted insulin), proinsulin and proinsulin ⁄C‐peptide ratio (PI/C) (markers of beta‐cell endoplasmic reticulum [ER] stress) with undercarboxylated (uOC) and carboxylated osteocalcin (cOC) and their ratio (uOC/cOC) in children with recently diagnosed type 1 (T1D) or type 2 diabetes (T2D), and the correlation of these variables with partial remission (PR) in children with T1D. Methods: Demographic and clinical data of children with new‐onset diabetes (n = 68; median age = 12.2 years; 33.8% non‐Hispanic White, 45.6% Hispanic/Latino, 16.2% African American and 4.4% other) were collected at diagnosis and during the first (V1), second (V2) and third clinical visits at 9.0, 32.0 and 175.7 weeks, respectively. Serum proinsulin, C‐peptide, uOC and cOC values were measured 7.0 weeks after diagnosis. PR was defined as insulin dose–adjusted HbA1c (IDAA1c) ≤9. Results: In children with new‐onset T1D with DKA (33.3%) or T2D (29.4%), Spearman's correlation coefficient revealed a positive association between the C‐peptide levels and both uOC and uOC/cOC ratio. In T1D (n = 48), both higher serum C‐peptide levels and low PI:C ratio were associated with higher BMI percentile ( β = 0.02, P = .001; β = −0.01, P = .02, respectively) and older age at diagnosis ( β = 0.13, P = .001; β = −0.12, P = .001, respectively). Furthermore, in children with T1D, C‐peptide levels at V1 correlated with IDAA1c ≤ 9 at V1 ( P = .04). Conclusion: C‐peptide levels are associated with a higher uOC and uOC/cOC ratio in paediatric diabetes. In new‐onset T1D children, older age and higher BMI were associated with lower beta‐cell stress and higher preserved function, which was predictive of PR on follow‐up. Abstract : We explored the association of C‐peptide, proinsulin and proinsulin ⁄C‐peptide ratio (PI/C) with undercarboxylated (uOC) and carboxylated osteocalcin (cOC), and their ratio (uOC/cOC) in children with recently diagnosed diabetes and the correlation of these variables with partial remission (PR) in children with T1D. In children with new‐onset T1D or T2D, residual beta‐cell function is associated with a higher uOC/cOC. In new‐onset T1D children, older age and higher BMI were associated with reduced beta‐cell stress and increased preserved function, which was predictive of PR on follow‐up.